2017
DOI: 10.1097/pts.0000000000000446
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Radio-Frequency Identification Technology on Patient Tracking in Hospitals: A Systematic Review

Abstract: The aim of this study was to systematically review all studies that evaluated the effects of using radio-frequency identification (RFID) for tracking patients in hospitals. Methods:The PubMed and Embase databases were searched (to August 2015) for relevant English language studies, and those that evaluated the effects of a real-time locating systems with RFID for patient tracking in hospitals were identified and extracted. Results:Of the 652 studies found, the 17 relevant studies were extracted for inclusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Distributing RTLS tags and enforcing their use in the community would be much more challenging than doing so in a clinical setting. Previous RTLS studies have been mainly confined to a defined setting [ 11 , 13 , 25 , 26 ]. On the other hand, Bluetooth technology is low cost, available on personal digital devices, and interoperable among Bluetooth-enabled devices [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Distributing RTLS tags and enforcing their use in the community would be much more challenging than doing so in a clinical setting. Previous RTLS studies have been mainly confined to a defined setting [ 11 , 13 , 25 , 26 ]. On the other hand, Bluetooth technology is low cost, available on personal digital devices, and interoperable among Bluetooth-enabled devices [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Technological advances such as real-time locating systems (RTLSs) have shown promise in overcoming the barriers to conventional contact tracing methods [13,14]. In recent years, health care institutions have been increasingly exploring the use of RTLSs to establish contacts within health care premises [12,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…An RTLS is an indoor positioning application that can locate a person or object tagged with radiofrequency identification (RFID) in real-time. 2 Some of its capabilities include tracking hospital assets, 3–5 monitoring patient safety for falls prevention, 6 , 7 monitoring hand hygiene compliance for infection prevention and control, 8 , 9 and contact tracing during an outbreak. 10 Studies on staff-worn RFID tags have shown promises in the accuracy and efficiency of RTLS technology for contact tracing compared with conventional methods.…”
Section: Background and Significancementioning
confidence: 99%